Participants reporting greater desire to have children demonstrate weaker preferences for younger adult faces - Jingheng Li; Pengting Lee; Benedict C. Jones; Victor K. M. Shiramizu (PLoS ONE, 2025)
The tendency for men to find younger adult women more attractive has been hypothesised to reflect preferences for cues of reproductive potential. To further test this hypothesis, we investigated the possible relationship between heterosexual men and women’s reported desire to have children and their preferences for cues of youth in face images of potential mates. Contrary to our expectation that reported desire to have children would be correlated with stronger preferences for younger adult faces, and that this pattern of results would be particularly pronounced when men judged women’s attractiveness, both men and women who reported greater desire to have children actually demonstrated weaker preferences for the faces of younger potential mates. Follow-up work suggested that this pattern of results was unlikely to have occurred because individuals with older faces were perceived as more likely to be better parents (Study 2) or wealthier (Study 3). While the role of individual differences in desire to have children in preferences for facial cues of age remains somewhat unclear, our results show no evidence for the widely held view that strong reliable sex differences exist in preferences for cues of youth.